Case report: Cytokine hemoadsorption in a case of hemophagocytic lymphohistiocytosis secondary to extranodal NK/T-cell lymphoma - Ruiz-Rodríguez, Juan Carlos; Chiscano-Camón, Luis; Ruiz-Sanmartin, Adolf; Palmada, Clara; Bajaña, Ivan; Iacoboni, Gloria; Bonilla, Camilo; García-Roche, Alejandra; Paola Plata-Menchaca, Erika; Maldonado, Carolina; Pérez-Carrasco, Marcos; Martinez-Gallo, Mónica; et al. (Frontiers in Medicine, 2022)
Hemophagocytic lymphohistiocytosis (HLH) is a severe hyperinflammatory syndrome induced by activated macrophages and cytotoxic T-cells. Secondary (acquired) HLH is the most frequent form in adults, commonly triggered by malignancies (up to 70%), Epstein-Barr Virus (EBV) associated lymphoma or infection. Untreated HLH can lead to rapid multiorgan dysfunction and death, so treatment should be started as soon as possible. The pathophysiology of organ dysfunction is led by the cytokine storm, so cytokine hemadsorption could have a potential therapeutic role in this setting.